Challenges of European Integration and the Fate of the Litas - Čepienė, Irena; Povilaitis, Bronius (Ekonomika, 2003)
The article presents a concise review of the potential development of the Bank of Lithuania and the litas within the context of Lithuania’s further integration in the European Union and the Economic and Monetary Union.The paper mostly focuses on the Exchange Rate Mechanism II as a period of transition from the litas to the euro and the preparation of the Bank of Lithuania and other national institutions for that step. The authors deal with theoretical and practical aspects of ERM n, present a review of European Central Bank requirements and analyse the Danish experience of its participation in the Mechanism. In addition, the article stresses the possibilities for the practical application of the Exchange Rate Mechanism and the expected impact on the future of the litas.From the starting date of their membership in the EU, the new Member States undertake a commitment of adopting the euro in due course. During the period of the participation in ERM II, these countries have to pursue such macroeconomic policies that would facilitate real and nominal convergence and would allow a country, wishing to adopt the euro, to meet Maastricht criteria.ERM II is an exchange rate policy system of euro area countries and EU Member States that have not adopted the euro. The key feature of the system is the central parity between the national currency of a country that has not adopted the euro vis-a-vis the euro. and the allowed exchange rate fluctuation band of ± 15 per cent in relation to that central parity. However. the European Commission and. more recently, the European Central Bank, have sought to narroW down the fluctuation band within ERM II (± 2,25%) with regard to the new EU Member States.The central bank of Denmark has managed to maintain a very stable exchange rate of the nacional currency against the euro throughout the whole period of its participation in ERM II since 1999 by using a significantly narrower fluctuation band than the adopted ± 2,25%. Lithuania is onc of the few EU candidate countries that already meets Maastricht requirements for the adoption of the euro. It is expected that Lithuania will join ERM II soon after assuming membership in the EU.The position of the Bank of Lithuania is that the present fixed exchange rale regime and the current official exchange rate between the litas and the euro of LTL 3.4528 for EUR I with a zero band is suitable for partiCipation in ERM II and the adoption of the euro.Regardless of certain differences between the operation of the currency board arrangement and the interventions undertaken in ERM II, the currency board arrangement is deemed to he an acceptable exchange rate regime for this Mechanism. After becoming a EU member from 1 May 2004, immediately joining ERM II and staying in it for at least two years, Lithuania will he meeting the requirements for the adoption of the euro. Thus, Lithuania would be in a position to give up the litas and adopt the euro in late 2006 or early 2007.